Mindreading Dysfunction in Avoidant Personality Disorder Compared With Other Personality Disorders. Issue 10 (October 2016) - Moroni, Fabio; Procacci, Michele; Pellecchia, Giovanni; Semerari, Antonio; Nicolò, Giuseppe; Carcione, Antonino; Pedone, Roberto; Colle, Livia
Abstract : Abstract: The ability to reflect on one's own states of mind and those of others (metacognition or mindreading) is strongly implicated in personality disorders (PDs). Metacognition involves different abilities, and there is evidence that specific abilities can be selectively impaired in different PDs. The purposes of this study were to compare metacognitive competence in avoidant PD (AvPD) with that in other PDs and to investigate whether there is a specific profile for AvPD. Sixty-three patients with AvPD and 224 patients with other PDs were assessed using the Metacognitive Assessment Interview. AvPD patients showed difficulties with two metacognitive functions: monitoring and decentration, even when the severity of psychopathology was controlled for. These results support the hypothesis of specific profiles of metacognitive dysfunction in different PDs and highlight a close link between impaired monitoring and decentration functions and the inhibited and withdrawn personality style typical of AvPD.